Sergei Bulgakov's Sophiology Historical Parallels and Ecumenical Dialogues - Kuznetsov, Michael Yurievich (Jurnal Multidisiplin Ibrahimy, 2026)
Sergei Bulgakov's sophiology offers a distinctive contribution to Russian religious philosophy by incorporating Divine Wisdom (Sophia) into Trinitarian theology, thereby bridging materialism and idealism while addressing the existential and theological crises of modernity. This study investigates historical parallels between Bulgakov's sophiological framework and ancient philosophical-theological traditions, aiming to demonstrate how these connections revitalize Orthodox theology and illuminate mediating principles in divine-human relations. An interdisciplinary methodology is applied, combining historical-philosophical analysis, comparative-theological examination, and detailed textual interpretation of primary sources. Bulgakov's major works are scrutinized alongside writings by early Christian figures (Origen, Arius, and Gnostic texts) and the Middle Platonist Plutarch, with attention to the socio-political context of early 20th-century Russia influencing Bulgakov's intellectual development. The comparative analysis uncovers profound parallels: Origen's emanationist theology and allegorical methods correspond to Bulgakov's portrayal of Sophia as a hypostatic bridge; Arius's emphasis on hypostatic distinctions echoes Bulgakov's non-hierarchical quadriform divine structure (God–Sophia–Holy Spirit–Son); Valentinian Gnostic aeonic emanations shape his fourfold essences; and Plutarch's daimonic intermediaries reflect Sophia's function in mediating between transcendent and immanent realms. The research asserts that: 1) Bulgakov innovatively retrieves and orthodoxizes ancient motifs, adapting emanationist and mediating principles to avoid heresy while enriching Trinitarian doctrine; 2) his sophiology critiques dogmatic rigidity and dualistic extremes, affirming the inherent divinity and goodness of creation; 3) this framework provides lasting relevance for contemporary theology, promoting mystical unity, ecumenical dialogue and a holistic understanding of human-divine interaction amid modern challenges.